Yield performance based selection of superior mutant lines from mutant wheat genotypes (Progressive Agriculture, 2019)
Wheat is the most widely grown cereal crop in the world. However, yield performance of wheat in Bangladesh is very low and the amount of cultivating land is decreasing drastically. Wheat cultivation in coastal saline regions can be a new dimension to increase the wheat production. Therefore, the first step of our research project was conducted out to evaluate the genotypic variability among the salt tolerant mutant lines of wheat genotypes to select superior lines based on yield performance on non-saline soil to bring them in the next step of screening process in salt affected areas. The performance of yield and yield contributing characters of 154 wheat genotypes were evaluated through Francis and Kannenberg’s method of selection. To evaluate the yield performance of mutant wheat lines, ‘Prodip’, a high yielding variety, developed by Bangladesh Agriculture Research Institute (BARI), was used as check variety. Thirty-seven wheat mutant lines, which perform better than ‘Prodip’ were selected based on yield contributing characters i.e. plant height, flag leaf duration, spike length, spikelet per spike, number of tillers, 100-grain weight and yield per plant. During selection of mutant lines, more emphasize given on the character 100-grain weight and yield per plant. The result of this study can be used for further evaluation of selected genotypes on saline soil before going to farmer level evaluation.Progressive Agriculture 30 (1): 10-19, 2019